FACTORS AFFECTING CONSUMERS TO CHOOSE 212 MART SURABAYA AS A PLACE TO SHOP - Iwan Prakoso Gunawarman; Ririn Tri Ratnasari (Universitas Airlangga, 2020)
This research aims to find out factors that influence consumers decision on shopping at sharia mart 212 Mart at Wonorejo, Surabaya in the middle of the rapid growth of 212 Mart’s franchise around Indonesia. The method used in this research is explorative factor analysis. The population’s charateristics used in this study are consumers of 212 Mart Surabaya and people that live around Wonorejo that ever trade at 212 Mart. The amount of sample that are used in this study are 30 respondents for the pre-eliminary test and 95 respondents for the main test. This research used convenience sampling to withdraw samples. This research found that there are five factors that influence consumers decision on shopping at sharia mart 212 Mart Surabaya. The factors are consumer compability of halal goods factor, recommendation from friends that has the same vision about 212 movement factor, inventory factor, parking area factor and Islamic atsmosphere factor.Keywords: Consumers Decisions, Sharia Mart, Compability of halal goods, Friend Recommendation, inventory, Parking Area, Islamic Atsmosphere.REFFERENCES Burns, Alvin C dan Ronald F. Bush. (2014). Marketing research seventh edition. Essex: Pearson Education Limited.Hayati, Asfarina. (2014). Faktor yang mempengaruhi keputusan konsumen muslim memilih hotel syariah grand kalimas Surabaya. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Hariadi, Guruh Taufan. (2016). Faktor-faktor yang Mempengaruhi Konsumen berbelanja di minimarket (studi pada indomaret dan alfamart di Semarang). Jurnal Penelitian Ekonomi dan Bisinis, 1(1), 6-32.Hikmawati, Dianur dan Chaikal Nuryakin. (2017). Keberadaan ritel modern dan dampaknya terhadap pasar tradisional di DKI Jakarta. Jurnal Ekonomi dan PembangunanIndonesia, 17(2), 195-208.Hussain, Riaz dan Mazhar Ali. (2015). Effect of Store Atmosphere on Consumer Purchase Intention. International Journal of Marketing Studies, 7(2), 35-43.Kementerian Agama Republik Indonesia. (2017). Al-Aqsha Mushaf Terjemah Tajwid Warna. Surabaya: UD Nur Ilmu.Khayruzzaman. (2016). Impact of religiosity on buying behaviour of financial products: a literature review. International Journal of Finance and Banking Research, 2(1), 18-23.Kotler, Phillip dan Gary Armstrong. (2016). Principles of marketing, 15th Edition. Harlow: Pearson Education Limited.——, dan Kevin Lane Keller. (2016). Marketing management, 15th Edition. Harlow: Pearson Education Limited.Madjid, Rahmat. (2014). The influence store atmosphere towards customer emotons and purchase decisions. International Journal of Humanities and Social Science Invention, 3(10), 11-19.Malhotra, Naresh K. (2010). Marketing research: an applied orientation Sixth Edition. New Jersey: Pearson Education, Inc.Moediarso, Hisnarilla Century. (2012). Pengaruh Karakter Amanah Amil Terhadap Niat Memilih Menjadi Donatur Tetap Pada Dompet Dhuafa Jawa Timur. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi Dan Bisnis Universitas Airlangga.Muflih, Muhammad. (2006). Perilaku Konsumen Dalam Perspektif Ilmu Ekonomi Islam. Jakarta: PT RajaGrafindo Persada.Omar, Ogenyi. (1999). Retail marketing. Essex: Pearson Education Limited.Othman, AbdulQawi dan Lynn Owen. (2001). Adopting and measuring customer service quality (sq) in Islamic banks: a case study in Kuwait Finance House. International Journal of Islamic Financial Services, 3(1), 1-26.Parasuraman, A, Valarie A Zeithaml dan Leonard L. Berry. (1998). Servqual: a multiple-item scale for measuring consumer perceptions of service quality. Journal of Retailing, 64(1), 12-40.Pusat Pengkajian Dan Pengembangan Ekonomi Islam (P3EI) Universitas Islam Indonesia Yogyakarta. (2014). Ekonomi Islam. Jakarta: PT RajaGrafindo Persada.Ratnasari, Ririn Tri. (2012). Manajemen pemasaran Islam. Modul 3. Surabaya: Departemen Ekonomi Syariah Fakultas Ekonomi dan Bisnis Universitas Airlangga.——, Fatin Fadhilah Hasib, dan Moh. Qudsi Fauzy. (2015). Religiousity on shopping orientation and behavioral intention for moslem and non-moslem customers. Surabaya: Departemen Ekonomi Syariah Fakultas Ekonomi Dan Bisnis Universitas Airlangga.Saraswati, S.H. (2017). Analisis dampak keberadaan minimarket indomaret dan alfamart terhadap UKM dalam kaitannya dengan peraturan presiden nomor 112 tahun 2007 tentang penataan dan pembinaan pasar tradisional, pusat perbelanjaan dan toko modern (studi di kota Pontianak). Jurnal NESTOR Magister Hukum, 4(4).Schiffman, Leon dan Leslie Lazar Kanuk. (2008). Perilaku Konsumen. Edisi 7. Jakarta: Indeks.Sezgin, Mete dan Senem Küçükköylü. (2014). Store’s Atmosphere’s Importance in Creating Store’s Image in Sustainable Management of Store and a Research in Konya (Turkey) City. Journal of Advanced Management Science, 2(3), 186-191. Doi: 10.12720/joams.2.3.186-191Sihombing, Sabrina O. (2011). Memprediksi Hubungan, Loyalitas Merek, Rasa Keikutsertaan, Kecocokan Citra Diri dan Konsumsi Terakhir Terhadap Kesejahteraan Konsumen: Studi Empiris Pada Kedai Kopi Starbucks (hal 192-207). Jurnal EKOBIS, 12(2).Sugiyono, (2018). Metode penelitian kuantitatif kualitatif dan R&D. Bandung: Alfabeta.Sula, Muhammad Syakir dan Hermawan Kartajaya. (2006). Syariah marketing. Bandung: PT Mizan Pustaka.Zaba-Nieroda, Renata. (2011). Developing Corporate Image. The Malopolska School of Economics in Tarnow Research Papers Collection. Issue 1/2011.Zikmund, William G dan Barry J babin. (2013). Menjelajahi riset pemasaran. Jakarta: Salemba Empat.